1996
DOI: 10.1093/clinids/23.5.1091
|View full text |Cite
|
Sign up to set email alerts
|

Erysipelas: Clinical and Bacteriologic Spectrum and Serological Aspects

Abstract: The bacteriologic, serological, and clinical characteristics of 229 patients with erysipelas diagnosed during a 2-year period at a university hospital for infectious diseases in Sweden are presented. Beta-Hemolytic streptococci were detected in 34% of these patients. Group A was the dominant serogroup, but group G streptococci were found in about half as many cases. Bacteremia was present in 5%. A serological response with antistreptolysin O (ASO) and antideoxyribonuclease B (ADNase B) was seen primarily in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
139
4
14

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(162 citation statements)
references
References 43 publications
4
139
4
14
Order By: Relevance
“…Erysipelas represents one of the primary clinical manifestations in patients with skin lesions and superficial wound infections and can probably be seen as a consequence of the increasing age and number of patients with underlying diseases with potentially impaired peripheral blood supply (diabetes mellitus or chronic heart and lung diseases) (9). A previous study found that only 10% of all erysipelas cases caused by GAS yielded a positive blood culture (13).…”
Section: Discussionmentioning
confidence: 99%
“…Erysipelas represents one of the primary clinical manifestations in patients with skin lesions and superficial wound infections and can probably be seen as a consequence of the increasing age and number of patients with underlying diseases with potentially impaired peripheral blood supply (diabetes mellitus or chronic heart and lung diseases) (9). A previous study found that only 10% of all erysipelas cases caused by GAS yielded a positive blood culture (13).…”
Section: Discussionmentioning
confidence: 99%
“…This possibility is corroborated by the finding of S. pyogenes in the renal tissue of two patients. This possibility might also be supported by the increased levels of AST and anti-DN:ase B in two patients suggesting a recent infection with GAS or possibly GCS [18][19][20]. S. constellatus is not, to our knowledge, known to produce streptolysin O or DN:ase B.…”
Section: Discussionmentioning
confidence: 97%
“…126 The most common causes of uncomplicated skin and soft tissue infections are group A bhemolytic Streptococcus and Staphylococcus aureus bacteria. [197][198][199][200][201][202] Data from the SENTRY Antimicrobial Surveillance Program monitoring skin and soft tissue infections indicated that S aureus was the most common pathogen among complicated and hospitalized patients, followed by Pseudomonas aeruginosa, Enterococcus, Escherichia coli, Enterobacter, Klebsiella, and Streptococcus.…”
Section: Identification Of Infection and Adverse Reactionsmentioning
confidence: 99%